Factors Affecting Taxpayer Compliance in Paying Natural and Building Taxes (Study in Datar Lebar II Village, Lungkang Kule District, Kaur Regency) - Elen Novita Maharani; Ida Anggriani; Herlin Herlin (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2021)
The purpose of this study is to find out whether income affects taxpayer compliance in paying land and building taxes (Study in Datar Lebar II Village, Lungkang Kule District, Kaur Regency). To find out whether awareness affects taxpayer compliance in paying land and building taxes (Study in Datar Lebar II Village, Lungkang Kule District, Kaur Regency). c. This is to find out whether the quality of service affects taxpayer compliance in paying land and building taxes (Study in Datar Lebar II Village, Lungkang Kule District, Kaur Regency). Based on the results of this study it is concluded that there is an effect of income (X1) on taxpayer compliance (Y) based on the results of the tsig test for variable income (X1) is 0.021, the calculated value is compared with the α value of 0.05 with a significant level of 0.021 < 5% for the income variable (X1) means that Ha is accepted and Ho is rejected, which means that there is an effect of income (X1) on taxpayer compliance (Y). There is an effect of awareness (X2) on taxpayer compliance (Y) based on the results of the t-test for the awareness variable (X2) which is 1.589 the value of the tcount when compared with the t-table of 1.6991. because tcount <ttable (1.589 <1.6991) with a significant level of 0.023> 5%, then Ha is rejected and Ho is accepted, which means the effect of awareness (X2) on taxpayer compliance (Y). There is an effect of service quality (X3) on audit quality (Y) based on the results of the t-test for the service quality variable (X3) which is 0.763, the value of the t-count when compared with the t-table of 1.6991 because tcount <ttable (0.763 <1.6991) with a significant level of 0.042 <5%, then Ha is accepted and Ho is rejected, which means that the effect of service quality (X3) on audit quality (Y).